VARIATIONAL METHODS IN IMAGE RECOVERY - Osorio Vidal, Víctor (2004)
We study the semicuadratic minimization problem of the formthis functional arises in image recovery problems, when aimage that describe a real scene, consider like a function f: ΩR2 → R, is observed and reproduced like a function p: Ω R2 → R.